Insulin resistance and secrection indexes in healthy Italian childrenand adolescents: a multicentre study - d'Annunzio, G.; Vanelli, M.; Pistorio, A.; Minuto, et al., N. (Acta Biomedica Atenei Parmensis, 2009)
Background and aim: To establish normal values of insulin resistance, secretion and sensitivity using respectively HOMA-IR, HOMA-β% and QUICKI indexes in healthy Italian children and adolescents, based on fasting samples. Methods: We determined HOMA-IR, HOMA-β% and QUICKI at baseline in 142 healthy subjects from Pediatric Centres, aged 2.7 to 19 years (10.6±3.8, Mean±SD), with different Tanner’s pubertal Stages (TS). None had hypo/hyperglycemia (fasting plasma glucose ranging from 3.6 to 5.6 mmol/l), obesity (BMI (kg/m2) 17.9±2.4, M±SD), or family history for diabetes mellitus. Results: The HOMA-IR index slightly increases with Tanner’s stage. As regards HOMA-β% and QUICKI, a weak variation throughout puberty was observed. No significant correlation was observed between HOMA-IR, HOMA-β%, QUICKI and BMI-SDS or chronologic age. Conclusions: Normal values of HOMA-IR, HOMA-β% and QUICKI are useful tools in the clinical and epidemiological practice for baseline screening and follow-up of subjects at risk for type 2 diabetes mellitus.